Biometrics of hoof balance in equids - Souza A.F.* (2016)
Differences in hoof balance between horses, mules and donkeys were identified in order to form more specific considerations for proper management of the animals. Measurements of the natural dimensions of hooves in sixty animals were used: 20 horses from the Crioulo breed, 20 mules and 20 donkeys from the Pêga breed. Liveweight was estimated using the correlation equations in each species by heart girth. Using a caliper rule, tape measure and hoof gauge, measurements of the length and width of the frog, hoof height, angle of heel, medial and lateral dorsal length, angle of the toe and crown circumference of the hooves of forelimbs and hindlimb were taken. Within each group the hooves of the hindlimbs exhibited narrower measurements than the hooves of the forelimbs and no difference was observed between the hoof angle of both members of groups. The conformation of the hooves of donkeys is shown to be substantially different from that observed in horses, the mules being in an intermediate condition, being smaller, angled and robust frog and proportionally more developed. Similarly, the hooves of donkeys provide greater support area compared to mules and horses, in descending order, even being dimensionally smaller. We conclude that the hooves of horses, mules and donkeys, have specific patterns of geometric balance that must be taken into consideration at the time of trimming and imbalance inferences.